PENINGKATAN KEMAMPUAN BERPIKIR KREATIF PADA PEMBELAJARAN IPAS DENGAN MENERAPKAN MEDIA SMART BOX - Kusumawati, Septia Dwi; Fatimah, Titim; Mahmud, Muhammad Rifqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low level of creative thinking skills among students in Natural and Social Sciences (IPAS). Of the 30 students, only 3 had achieved KKTP, while the other 27 had not. The factor influencing the low level of creative thinking skills among students was that the learning media used did not fully provide space for creating new ideas. One learning medium that can improve creative thinking skills is the smart box learning medium. This study aims to determine students' creative thinking skills before and after using the smart box medium and how the smart box medium is applied in Natural and Social Sciences in grade IV at SDN Kencana Indah I. The approach used in this study is quantitative and qualitative. The method used in this study was the classroom action research method. This study was conducted in four cycles, and the subjects in this study were 30 fourth-grade students at SDN Kencana Indah I. Data collection techniques included observation, interviews, tests, and documentation. The results showed that in the pre-cycle stage, classical mastery was only 23% with an average score of 60. Teacher activity increased from 64% in cycle I to 100% in cycle IV, while student activity increased from 63% to 96%. Classical mastery also increased, namely cycle I 17% (average 64), cycle II 60% (76), cycle III 83% (77), and cycle IV 90% (80). Overall, classical mastery reached 67% with an average score of 76. Based on these results, the smart box media proved to be effective in improving students' creative thinking skills in IPAS learning.